6r+3=8r+11

Simple and best practice solution for 6r+3=8r+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6r+3=8r+11 equation:


Simplifying
6r + 3 = 8r + 11

Reorder the terms:
3 + 6r = 8r + 11

Reorder the terms:
3 + 6r = 11 + 8r

Solving
3 + 6r = 11 + 8r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-8r' to each side of the equation.
3 + 6r + -8r = 11 + 8r + -8r

Combine like terms: 6r + -8r = -2r
3 + -2r = 11 + 8r + -8r

Combine like terms: 8r + -8r = 0
3 + -2r = 11 + 0
3 + -2r = 11

Add '-3' to each side of the equation.
3 + -3 + -2r = 11 + -3

Combine like terms: 3 + -3 = 0
0 + -2r = 11 + -3
-2r = 11 + -3

Combine like terms: 11 + -3 = 8
-2r = 8

Divide each side by '-2'.
r = -4

Simplifying
r = -4

See similar equations:

| -x=0.25 | | 6(x+3)=18+6x | | 10x-18x= | | 7a/8+2/7=a/2-6/7 | | 1/16*6/1 | | 10x-(7x+4)-5x=16 | | -6x^2+26x+60=0 | | 60(x-6)=36(x+6) | | 4y+18y=198 | | 812x=x+17 | | 434= | | ln(400/A)=x*ln(1.04/x) | | -6m-6=-6m-6 | | 11x-(-2x-11)=7+8x | | 0.10(x+200.00)=55.00 | | (x+4)/(3x+12)=0 | | x+5(x-2)=14 | | -3.2a=-5.68 | | 5x-11x=42 | | 2e^8x=7 | | 0.10(x+200.10)=100.00 | | x^2+26x+60=0 | | 3-6r=15 | | 4p+13p=85 | | 4(x-1)-(5x-8)=2(4x-1)-3 | | 5-5=13x+3x | | 1/3b-3=b+9 | | 24/7*8 | | 1-1=2(1-h) | | 1-1=1(1-h) | | b+(-3)=8 | | 4v^2-48v-52=0 |

Equations solver categories